Radical Acts of Re-imaging Ethical Relationality and Trans-systemic Transformation - Kelly, Vicki (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
This Indigenous métissage explores my engagement in Indigenous Arts-based Inquiry as a practice of Anishinaabe Ozihtoon or Indigenous making and knowledge generation. Anishinaabe Ozhitoon is a site that unlocks the theoretical potentialities of the intelligences within Indigenous Knowledge practices in contemporary contexts and reanimates Indigenous land-based assurgence. Reviving Indigenous artistic practices, as sites of co-imagining through constellations of co-creation, is part of ecological and community-based reconciliation and healing. Key to this process is the act of reciprocal recognition, a core practice that fosters ethical relationality, helps cultivate our Indigeneity, and honours the circle of life. This Indigenous métissage tracks the Indigenous pedagogical processes and Indigenous art making used in my own praxis and inquiry as a scholar while I worked in a university to create three pathways for trans-systemic knowledge creation: a university-wide President’s Dream Colloquium with an accompanying graduate course; a graduate diploma in Indigenous Education: Education for Reconciliation and a master’s in Indigenous Education: Truth, Reconciliation, and Indigenous Resurgence; and the Indigenous Research Institute initiation of an Indigenous Ethics Dialogue process as a trans-systemic pedagogical engagement with Indigenous and Western Knowledges, values, and ethics.